Kemampuan Pemecahan Masalah Siswa melalui Pendekatan Contextual Teaching and Learning di Kelas X SMK Negeri 1 Bireuen - Diah Setiawati (Universitas Syiah Kuala, 2017)
This study aimed to determine: (1) the difference upgrades between the problem solving ability of students receiving learning approach through Contextual Teaching and Learning (CTL) and students receiving learning through conventional learning, (2) interaction of learning approach and early mathematics ability (high, medium and low) to increase students' problem-solving abilities. This study is a semi-experimental study. The study population was a class X student of SMK Negeri 1 Bireuen, and analysis with two lines ANOVA analysis and t-test. The results showed that (1) there are differences in improvement between the students' problem-solving skills that students acquire learning approach CTL with increased problem-solving ability of students receiving conventional learning, (2) there is no interaction between teaching approaches used and early math abilities of students to increase students' problem-solving abilities.